Effect of diatoms blooms to human health and environment / Nur Hafizah Hisham ... [et al.] - Hisham, Nur Hafizah; Jamaludin, Siti Nur Syifaa; Rahizar, Nurshahirah; Abd Malek, Alyssa Safiyah; Abdul Aziz, Nur Syawanie; Shukor, Siti Nur Shazwani; Noor Hisham, Aida Qasrina; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Diatoms are a type of phytoplankton, which are microorganisms that contain chlorophyll and require sunlight to live and grow. They are unicellular, and photosynthetic organisms of various colors, and diverse forms. Diatoms come under the kingdom Protista which is called as photosynthetic protists. Photosynthetic protists are mostly planktonic in which they grow and cover the surface of the water body and move on the mercy of water currents. Diatoms belong to the group of algae known as "hard algae" due to its silica frustule which is sometimes covered with spikes, thorns, or spines (Scotese, 2019). A frustule is the external, siliceous part of the diatom cell wall. Diatom blooms as shown in Figure 1 are dynamic system events in which some singlecelled photosynthetic organisms that can take advantage of both biotic and abiotic conditions becoe dominant. This is caused by a combination of high nutrient concentrations and elevated temperatures.